Binary mixture effects by PBDE congeners (47, 153, 183, or 209) and PCB congeners (126 or 153) in MCF-7 cells: biochemical alterations assessed by IR spectroscopy and multivariate analysis - Llabjani, Valon; Trevisan, Júlio; Jones, Kevin C; Shore, Richard F; Martin, Francis L (Environmental science & technology, 2010)
Target organisms are continuously and variously exposed to contaminant mixtures in the environment. We noted that treatment with brominated diphenyl ether (BDE)47 or polychlorinated biphenyl (PCB)126 (toxic equivalency factor [TEF] = 0.1) induces similar alterations in MCF-7 cells when these were determined using attenuated total reflection Fourier-transform infrared (ATR-FTIR) spectroscopy with multivariate analysis. Because this method appears sensitive enough to signature low-dose effects, we examined how various test agents interact in binary mixtures to induce cell alterations. MCF-7 cells were exposed for 24 h to low concentrations (10(-12) M) of polybrominated diphenyl ether (PBDE) congeners (47, 153, 183, or 209) with or without the coplanar PCB126 or nonplanar PCB153. Following treatment, ethanol-fixed cellular material was interrogated using ATR-FTIR spectroscopy; derived IR spectra in the biochemical-cell fingerprint region (1800 cm(-1)-900 cm(-1)) were then subjected to principal component analysis-linear discriminant analysis. Assuming that if two test agents independently induce the same cell alteration that in combination they'll give rise to an additive effect, we examined predicted versus observed differences in induced alterations by binary mixtures. Compared to corresponding control clusters, treatment with PBDE congener plus PCB126 appeared to cancel out their respective induced alterations. However, treatment with binary mixtures including PCB153 gave rise to an enhanced segregation. Our findings suggest that test agents which mediate their cellular effects via similar mechanisms might result in inhibition within a binary mixture whereas independently acting agents could exacerbate induced alterations in overall cell status.